Responsabilidad social de los medios digitales y su impacto en la opinión de los habitantes del cantón Ventanas, año 2022 - Castro Castro, Dalton Adrian (2022)
At present, paper newspapers are gradually heading towards the end of their days, it is worth looking at who, possibly, can transform this journalistic industry: young people. This work reviews the reasons that explain the distance between young people and the press and observes how they are represented in this medium. After the content analysis of the digital media of the Ventanas canton, the results show that they are widely accepted by the inhabitants of the canton mentioned above. Digital networks have not only facilitated communication between people by configuring a nodal system in which they no longer have geographical barriers between humans, but they have also become the most effective tool today for sharing and disseminating content across global scale. However, in addition to the imbalance in the economic participation of the different actors in the value chain of creative content, this greater dissemination and use on a large scale has brought with it an increasing illicit use of works and performance. In this regard, creative sectors have often wondered how to build a participation system that generates a balance between creators, artists, producers, digital platforms and content users?